Physical condition of the students of the first semester of the Professional in Sports program of the Colombian Polytechnic Jaime Isaza Cadavid (2022)
The study presented was oriented to the measurement of the physical condition of the students of the Professional Program in Sports who begin their university life in the institution, with a population of 63 students and a sample of 43 (61%). To carry out the analysis, students were characterized and specific tests were applied to assess the level of physical condition such as aerobic power, muscle strength and flexibility. It was found that the group in general is below normal in relation to physical condition, showing that of the 5 tests performed, two of them (Vo2max and power of lower limbs) presented a range characterized as normal), while three of them (upper limb strength, abdominal strength and flexibility), presented poorly results.